2020
DOI: 10.1007/s10072-020-04604-1
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular complications following targeted therapy in cancer patients: beyond the immune checkpoint inhibitors. Case reports and review of the literature

Abstract: Introduction In the last years, many new drugs have been developed targeting different oncology pathways, overall improving both quality of life and survival in several malignancies. However, the increase of those therapies is associated with novel toxicities, mainly immune-related adverse events (irAEs), never observed before. Different irAEs are now well characterized, and, among them, neuromuscular complications, following immune checkpoint inhibitor (ICPi) therapy, are increasingly studied and described. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…From the literature search, seven reports were identified (six case reports and one case series) that describe 12 cancer patients who developed MG after targeted therapy (15)(16)(17)(18)(19)(20)(21). The included articles were all retrospective studies, so the assessment of quality and risk of bias of analysis were performed using the 9-point Newcastle-Ottawa Scale (NOS) (Table 1).…”
Section: Literature Review Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From the literature search, seven reports were identified (six case reports and one case series) that describe 12 cancer patients who developed MG after targeted therapy (15)(16)(17)(18)(19)(20)(21). The included articles were all retrospective studies, so the assessment of quality and risk of bias of analysis were performed using the 9-point Newcastle-Ottawa Scale (NOS) (Table 1).…”
Section: Literature Review Resultsmentioning
confidence: 99%
“…In this class of TKIs, Demichelis et al reported a case of a 65year-old man with a gastrointestinal stromal tumor (GIST) who commenced imatinib on adjuvant setting following an initial resection of the tumor (17). A few days after initiation of targeted therapy, the patient presented with dysphagia and weakness of the neck extensor muscle, which subsided after a 2-day pause of TKI.…”
Section: Inhibitors Of Fused Breakpoint Cluster Region and Abelsonmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Apart from this, only few case reports are present in the literature. [14][15][16][17][18][19] The incidence of PN in cancer patients is elevated due to several mechanisms, including the neurotoxic potential of antineoplastic agents. 20 Although often neglected, PN can severely impact the quality of life of cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…Such analyses have been carried out for statins [6], checkpoint inhibitors [7], antibiotic drugs [8], and psychiatric and antiepileptic drugs [9]. Cardiovascular drugs rank high on cautionary lists.…”
Section: Introductionmentioning
confidence: 99%